The Safety Profile of Amiodarone Among Older Adults (Age ≥75 Years): A Pharmacovigilance Study from the FDA Data - Lerman, Tsahi T.; Gadot, Chen; Greenberg, Noam; Kruchin, Boris; Rahat, Ori; Buturlin, Kirill; Erez, Aharon; Goldenberg, Gustavo; Barsheshet, Alon; Golovchiner, Gregory; Orvin, Katia; Eisen, Alon; et al. (The American journal of medicine, 2025)
Amiodarone is a widely used antiarrhythmic agent with significant toxicities and drug interactions more likely to affect older adults. Nevertheless, data regarding amiodarone safety in this population are limited. We conducted a retrospective analysis of FDA [Food and Drug Administration] Adverse Event Reporting System (FAERS) data from 2003 to 2024. Reports with amiodarone as the primary suspect were compared with other antiarrhythmics (sotalol, dronedarone, flecainide, propafenone, dofetilide). Disproportionality analysis assessed reporting odds ratios (RORs) for predefined adverse events in adults (<75 years) and older adults (≥75 years). Interaction analysis evaluated differences between age groups. Among 9196 amiodarone FAERS reports, 4129 (44.9%) involved older adults. Hyperthyroidism (ROR 39.1; 95% confidence interval [CI], 25-61 and ROR 23.4; 95% CI, 11-49.8) and hypothyroidism (ROR 36.9; 95% CI, 15.2-89.8 and ROR 24.5; 95% CI, 11.5-52.1) were substantially over-reported in amiodarone users among both adults and older adults, respectively. Drug-induced liver injury and peripheral neuropathy were also over-reported without a significant age interaction. Interstitial lung disease was reported more frequently in amiodarone users overall, with significantly higher reporting in older adults (ROR 11.4; 95% CI, 6.9-18.6 vs 4.9; 95% CI, 3.4-7.0; Pinteraction = .007). Bradycardia was also over-reported in older adults compared with adults (ROR 1.6; 95% CI, 1.3-2 vs 1.0; 95% CI, 0.8-1.3; Pinteraction = .003). Torsades de pointes/QT prolongation were less frequently reported in both age groups. In this global postmarketing study, interstitial lung disease and bradycardia were more frequently reported in older adults treated with amiodarone. These findings support vigilant monitoring for these adverse events, particularly in older patients.